Severe Hypofunction of Allogeneic Hematopoietic Stem Cell Transplant in Patients with Oncohematological Diseases: Incidence, Risk Factors, and Outcomes - TA Rudakova; AD Kulagin; OU Klimova; IK Golubovskaya; EI Darskaya; TA Bykova; AG Smirnova; EV Morozova; SN Bondarenko; IS Moiseev; AV Beinarovich; DE Pevtsov; et al. (Клиническая онкогематология)

(untitled)
Aim. Based on strict criteria, to assess incidence, pretransplantation risk factors, and outcomes of severe hypofunction of graft, i.e. poor graft function (sPGF), following allogeneic hematopoietic stem cell transplantation (allo-HSCT) in adults.